The Students' Learning Strategies in Learning a Foreign Language through a Controlled Natural Practice with Foreigners - Ningsih, Retno Wahyu; Adriani, Diyan; Miharti, Isra (Indonesian Research Journal in Education |IRJE|, 2023)
This research aimed to describe the English learning strategies of English Education Study Program students inside and outside the classroom, how students used English in daily communication, and how students acted as tour guides in Yogyakarta. This qualitative research obtained the data from interview protocol and audio-visual recordings. The results showed that students were not aware of the language learning strategies used. Most students had difficulties in communicating by using English in the class because of their unsupported environment. However, they were able to communicate outside the classroom. They used memory and social strategies, followed by metacognitive and cognitive strategies. In these strategies, the participants gave a large second portion after the memory strategies. It showed that students still tended to be controlled by memory and awareness of the ability to use English. Affective strategies took the third sequence. Two strategies related to this social environment were applied by participants with different portions of the previous strategies.